Islamic Boarding School Accounting Practices in the Framework of Realizing the Quality of Islamic Boarding School Financial Reports - Zalikha; Ivvon Septina Bella; Noviyanti; Murni; Zulfahmi (IJCS: International Journal of Community Service, 2022)
The Aceh government designated Bireuen Regency as a santri city which was declared to coincide with the commemoration of the 6th National Santri Day (HSN) on October 22, 2020. This was done because Bireuen Regency is an area that has the largest number of Islamic boarding schools compared to other districts in Aceh with the number of santri which reached 51 thousand people. IAI has issued a financial reporting standard for Islamic Boarding Schools, namely Islamic Boarding School Accounting Guidelines which became effective in May 2018 which aims to facilitate Islamic Boarding Schools in preparing their financial reports, and can provide added value for the progress of Islamic Boarding Schools. The goal to be achieved in this program is how to apply the skills of SMPS Islam Darul 'Ulum Tanoh Mirah administrators so that they have skills regarding accounting practices based on Islamic Boarding School. The method used is Participatory Based learning, namely learning activities that involve teams and partners starting from the planning, implementation, monitoring and evaluation stages of the program. The activity plan is carried out in the form of accounting and management learning and training which is carried out both in theory and practice. The method used is Participatory Based learning, namely learning activities that involve teams and partners starting from the planning, implementation, monitoring and evaluation stages of the program. The activity plan is carried out in the form of accounting and management learning and training which is carried out both in theory and practice.